“La psicomotricidad en el desarrollo de la lectoescritura en los estudiantes de segundo año EGB Paralelo “A” de La Unidad Educativa “Amelia Gallegos Díaz”, Riobamba Periodo 2017- 2018.” - Calle Rodas, Erika Jazmín (2019)
In this research we worked with a group of 28 students belonging to the second year of basic general education "A" parallel of the Educational Unit Amelia Gallegos Diaz of the city of Riobamba with the purpose of determining the importance of psychomotor activities in the development of the literacy of the aforementioned students, by the characteristics that the present work has according to the level or scope is diagnostic-exploratory, descriptive and correlational, for the objectives it is basic, for the time it is transversal and for the place it is bibliographic and of field, in addition in the research development the analytical-synthetic method was used. For the collection of data necessary to direct the proposed exploration, the observation technique was used and the most appropriate instrument was chosen, which was the observation card. Once the work was done, it was determined that the application of psychomotor activities has a significant influence on the development of the literacy learning process, which is the correspondence between reading and writing as actions in which cognitive skills and abilities are developed. whose bases are each of the areas of psychomotricity so it is of vital importance its application from very early ages.